Keterbukaan Informasi Publik dalam pembangunan Kalimantan Timur - Sy. Nurul Syobah; M. Abzar. D; A. Rivai Beta; Imran Duse; Indra Zakaria (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
To create a prosperous and clean Indonesia, the state must be responsible for providing simple access to public information. In supporting the provision of public information openness, East Kalimantan plays an active role, as the East Information Commission institution carries out outreach and educational activities related to public information openness. One of these activities is a public discussion about the openness of public information in East Kalimantan, in collaboration with UIN Sultan Aji Muhammad Idris Samarinda (UINSI Samarinda). We hope that this activity will heighten public awareness and foster active participation in the disclosure of public information. This will certainly increase public trust in the government, and the community can contribute to policy and decision-making, especially in East Kalimantan.